Assessment of Seed Protectants in Respect to Quantitative Losses Due to Callosobruchus chinensis Linn in Stored Pigeon Pea - Shukla, P. K.; Patel, Shweta; Singh, R.B.; Rajput, S.K.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
To test the efficacy of seven tested seed protectants viz., Spinetoram, Flupyradifurone Emamectin benzoate, Deltamethrin, Neem oil, Dry Neem Leaf and Azadirachtin along with control were used against Callosobruchus chinensis Linn in stored pigeon pea under ambient condition in Seed Entomology laboratory, ANDUAT, Ayodhya during year 2021-22. All the seed protectants were evaluated for their effectiveness on the basis of seed damage, seed weight and seed moisture against pulse beetle under ambient condition for a period of 2, 4 and 6 months. Among tested seed protectants the Emamectin benzoate 5 SG followed by Spinetoram 11.7 SC and Neemoz Gold 1EC was found most effective as seed protectants with least seed damage and weight loss of seed up to 6 months of storage.